Care Professionals Manage the Future, Frail Older Persons the Past. Explaining Why Frailty Management in Primary Care Doesn't Always Work - La Grouw, Yvonne; Bannink, Duco; van Hout, Hein (Frontiers in Medicine, 2020)
Frailty management focuses on optimizing the physical and psychological functioning of older people with frail health through early risk identification and intervention in primary care. Such care programs demand a joint effort by primary care professionals and older persons, one in which professionals are expected to promote or facilitate self-management practices and older persons are expected to adhere to the professional advice. It is known that patients and professionals hold different perspectives on frailty, but we know little about how this may affect their cooperation in frailty management. In this article, we therefore study how different perspectives of older persons and their primary care professionals play a role frailty management in practice. Nine cases of frailty management were reconstructed through semi-structured interviews with older persons, their family doctor and practice nurse. Drawing from literature on managing complex problems, we analyzed how “factual” and “normative” orientations played a role in their perspectives. We observe that the perspectives of care professionals and older persons on frailty management were fundamentally different. Primary care professionals employed practices to manage the medical and social factors of frailty in order to prevent future loss. Older persons employed practices to deal with the psychological, emotional and social aspects of the different types of loss they already experienced in order to reconcile with loss from the past in the present. Both actors “manage” frailty, but they focus on different aspects of frailty and interestingly, care professionals’ rationale is future-oriented whereas older person’s rationale past-oriented. These findings raise fundamental questions regarding the different perceptions of and priorities around not only care for frail older people in general, but also implied professional-patient relations and the value of a risk-management approach to care for older people with frail health. The distinction between these perspectives could help care professionals to better respond to older patients’ preferences and it could empower older persons to voice preferences and priorities that might not fit within the proposed care program.